Bike Lane Design for Bicyclists and Bike Sharing in Bandung City - Weningtyas, Widyarini; Aulia, Qiranawangsih; Adriani, Lestari H.; Nurlayla, Arbie (CSID Journal of Infrastructure Development, 2015)
Cycling is now growing in Bandung City, Indonesia. One of the popular programs is bike sharing which was established in 2012. Recently, the bike sharing program has revealed a plan to develop bike stations and bike lanes. Thus, the bike lane plan needs to be adjusted with the Indonesian Design Standard for Bike Lanes. The standard takes into account physical characteristics of the roads/streets. It was found that most of the roads/streets on the list are not suitable for bike lanes; only 42 out of 151 are qualified. This means in order to encourage cycling activities, although it is not included in bike sharing program, the physical characteristics of roads/streets and sidewalks need to be developed.